EFEKTIVITAS FUNGSI KOORDINASI DAN SUPERVISI DALAM PENYIDIKAN TINDAK PIDANA KORUPSI OLEH KOMISI PEMBERANTASAN KORUPSI - Hibnu Nugroho (Jurnal Dinamika Hukum, 2013)
The establishment of KPK (Corruption Eradication Commission) as an institution is aimed neither to settle every corruption case nor to monopolize every corruption case settlement on court. KPK was initiated as a trigger mechanism institution in the corruption case settlement to the law enforcer institution. Therefore, the authority and responsibilities of KPK are to coordinate and to supervise. Article 6 point a and b No. 30 year 2002 concerning the coordination and supervising function mentioned above. Both has important role on the corruption cases investigation in the region. Up to now, these functions are not maximally executed by KPK. Year-by-year sub-division of coordination and supervision of KPK has a specific target to be done; nonetheless, there are lot of police and attorney investigators who are assigned to handle the corruption cases in the region state that the execution of these functions are still far from expectation. Key words: coordination, supervision, corruption investigation